2006
DOI: 10.1007/s10573-006-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

Metal-particle ignition and oxide-layer instability

Abstract: The use of metals as high-energy fuel additives is generally compromised by the appearance of a strongly protective oxide layer that covers the fuel surface. The previous work concentrated on the elimination of the oxide layer by a global, symmetryconserving attack, using an admixture of aggressive chemical constituents in the ambient atmosphere, a strong flux of radiation, or strongly shearing gas flows designed to intensely strain the surface layer. This paper shows that symmetry breaking leads to a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the past five decades, ignition of metal fuels has been investigated both experimentally and theoretically in detail [1][2][3][4][5][6], and of significant practical interest is aluminum since aluminum fuels possess the advantages of high oxidation enthalpy and combustion temperature, environmentally friendly by-products and relatively low cost [7][8][9][10]. Micronsized aluminum fuels have been intensively applied in various energetic materials, including pyrotechnics, explosives, and propellants [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the past five decades, ignition of metal fuels has been investigated both experimentally and theoretically in detail [1][2][3][4][5][6], and of significant practical interest is aluminum since aluminum fuels possess the advantages of high oxidation enthalpy and combustion temperature, environmentally friendly by-products and relatively low cost [7][8][9][10]. Micronsized aluminum fuels have been intensively applied in various energetic materials, including pyrotechnics, explosives, and propellants [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The whole oxidation process can be explained according to the changing properties of the external alumina layer. 38 Rai et al 39 found that the oxidation was due to the diffusion of species, which took place in two regimes separated by the melting temperature of the metal particles. The first regime was slow and occurred before the melting whereas the second regime was fast occurring after the melting.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Many important results have been obtained in these directions which are still subjects of ongoing intensive experimental and theoretical studies. [8][9][10][11][12][13][14][15] Yet, the large amount of energy released by a burning metal has undesirable consequences and represents a source of significant fire hazards, especially when metals are used in high-temperature and/or high-pressure oxidizing environments such as those prevailing in nuclear plants and oxygen supply systems. 16,17 The research conducted in metal-fire prevention has mostly consisted of carrying out standard tests that quantify the relative flammability of different metals, that is, their relative propensity to sustain combustion of metallic materials of standardized dimensions in oxygen atmospheres.…”
Section: Introductionmentioning
confidence: 99%